(untitled) (Research, Society and Development, 2020)
The university extension allows the execution of activities developed between the university and the community as a means of social and professional transformation. This article corresponds to an account of a psychopedagogical experience with the use of assistive technologies in a hospital class of the university extension project - “Psychopedagogical assistance to hospitalized children and adolescents”, coordinated by teacher PhD. Janine Marta Coelho Rodrigues. Project carried since 2001 at the Lauro Wanderley University Hospital (HULW-UFPB), located in Brazil, in the city of João Pessoa - PB. This research portrays the use of assistive technologies in psychopedagogical assistance, as well as inclusive pedagogical practices and their relevance for autonomy and cognitive development of these students/patients. We highlight how pertinent the study of this article is, its importance within education and how much we need to fight for the education that belongs to everyone. The methodological proposal of this study involved a bibliographic and observation research, being built in a qualitative perspective, using content analysis as a method of analysis.